Between Colonizer and Colonized: An Exploration of Hybridity and Mimicry in Robinson Crusoe - Bhatta, Arjun Dev (KMC Journal, 2026)
This research article critically examines the complex and ambivalent relationship between colonizers and the colonized in Daniel Defoe’s Robinson Crusoe. It aims to unravel the contradictions and anxieties embedded in colonial authority. To support this claim, the researcher draws on theoretical insights forwarded by postcolonial theorist Homi K. Bhabha in his seminal text ‘The Location of Culture’. Bhabha’s concepts of hybridity, mimicry, ambivalence, and ‘The Third Space’ are employed as key theoretical tools to show how colonial authority is disrupted and resisted. Focusing on Crusoe-Friday relationship, the article argues that Friday’s mimicry and hybridity unsettle Crusoe’s authority and open up a ‘Third Space’ for cultural negotiation and resistance. This article follows a qualitative research method, analyzing the text through primary and secondary resources available in the library and online resources. Using Bhabha’s postcolonial theory, particularly his notions of hybridity and mimicry, this article seeks to fill up the gap left by earlier research. The findings of the study suggest that Defoe’s Robinson Crusoe is not a monolithic narrative of European superiority but a text that reveals the fragility and complex colonial discourse.